Cancer patients' needs assessment in primary care: study protocol for a cluster randomised controlled trial (cRCT), economic evaluation and normalisation process theory evaluation of the needs assessment tool cancer (CANAssess). Issue 5 (4th May 2022) - Clark, Joseph; Copsey, Bethan; Wright-Hughes, Alexandra; McNaught, Emma; Bijsterveld, Petra; McCormack, Terry; Foy, Robbie; Wilkes, Scott; Dickson, Jon Mark; Meads, David; Farrin, Amanda; Johnson, Miriam
Abstract : Introduction: Unmet needs in patients with cancer and their carers are common but poorly identified and addressed. The Needs Assessment Tool-Cancer (NAT-C) is a structured consultation guide to identify and triage patient and carer unmet needs. The NAT-C is validated, but its effectiveness in reducing unmet patient and carer needs in primary care is unknown. Methods and analysis: Cluster randomised controlled trial with internal pilot and embedded process evaluation to test the clinical and cost effectiveness of the NAT-C in primary care for people with active cancer in reducing unmet patient and carer need, compared with usual care. We will recruit 1080 patients with active cancer (and carers if relevant) from 54 general practices in England. Participating practices will be randomised 1:1 to either deliver an NAT-guided clinical consultation plus usual care or to usual care alone. Consenting participants with active cancer and their carers (if nominated) will be asked to complete study questionnaires at baseline, 1 and 3 months for all, 6 months except for those recruited outside of the last 3 months of recruitment, and attend an NAT-C appointment if allocated to an intervention practice. An internal pilot will assess: site and participant recruitment, intervention uptake and follow-up rates. The primary outcome, the proportion of patients with an unmet need on the Supportive Care Needs Survey Short Form 34 at 3 months postregistration, will be analysed using a multilevel logistic regression. Mixed-methods process evaluation informed by Normalisation Process Theory will use quantitative survey and interview data from clinicians and key stakeholders in cancer care to develop an implementation strategy for nationwide rollout of the NAT-C if the intervention is cost-effective. Ethics and dissemination: Ethical approval from London-Surrey REC (20/LO/0312). Results will be peer-reviewed, published and made available to research participants. Trial registration number: ISRCTN15497400 .